Allogeneic Mesenchymal Stromal Cells (MSCs) are of Comparable Efficacy to Syngeneic MSCs for Therapeutic Revascularization in C57BKSdb/db Mice Despite the Induction of Alloantibody. Issue 8 (August 2018) - Liew, A.; Baustian, C.; Thomas, D.; Vaughan, E.; Sanz-Nogués, C.; Creane, M.; Chen, X.; Alagesan, S.; Owens, P.; Horan, J.; Dockery, P.; Griffin, M. D.; et al.
Intramuscular administration of mesenchymal stromal cells (MSCs) represents a therapeutic option for diabetic critical limb ischemia. Autologous or allogeneic approaches may be used but disease-induced cell dysfunction may limit therapeutic efficacy in the former. Our aim was to compare the efficacy of allogeneic and autologous MSC transplantation in a model of hindlimb ischemia in diabetes mellitus and to determine whether allogeneic transplantation would result in the activation of an immune response. MSCs were isolated from C57BL/6 (B6) and diabetic obese C57BKS db/db mice. Phosphate-buffered saline (control group), and MSCs (1 × 10 6 ) from B6 (allogeneic group) or C57BKS db/db (syngeneic group) were administered intramuscularly into the ischemic thigh of C57BKS db/db mice following the induction of hindlimb ischemia. MSCs derived from both mouse strains secrete several angiogenic factors, suggesting that the potential therapeutic effect is due to paracrine signaling. Administration of allogeneic MSCs significantly improved blood perfusion as compared with the control group on week 2 and 3, post-operatively. In comparison with the control group, syngeneic MSCs significantly improved blood perfusion at week 2 only. There was no statistical difference in blood perfusion between allogeneic and syngeneic MSC groups at any stages. There was no statistical difference in ambulatory and necrosis score among the three groups. Amputation of toes was only observed in the control group (one out of seven animals). Alloantibody was detected in three out of the eight mice that received allogeneic MSCs but was not observed in the other groups. In summary, we demonstrated comparable efficacy after transplantation of autologous and allogeneic MSCs in a diabetic animal model despite generation of an immune response.